Tuning and disrupting the brain—modulating the McGurk illusion with electrical stimulation - Marques, Lucas Murrins; Lapenta, Olivia Morgan; Merabet, Lotfi B.; Bolognini, Nadia; Boggio, Paulo Sérgio (Frontiers in Human Neuroscience, 2014)
In the so-called McGurk illusion, when the synchronized presentation of the visual stimulus /ga/ is paired with the auditory stimulus /ba/, people in general hear it as /da/. Multisensory integration processing underlying this illusion seems to occur within the Superior Temporal Sulcus (STS). Herein, we present evidence demonstrating that bilateral cathodal transcranial direct current stimulation (tDCS) of this area can decrease the McGurk illusion-type responses. Additionally, we show that the manipulation of this audio-visual integrated output occurs irrespective of the number of eye-fixations on the mouth of the speaker. Bilateral anodal tDCS of the Parietal Cortex also modulates the illusion, but in the opposite manner, inducing more illusion-type responses. This is the first demonstration of using non-invasive brain stimulation to modulate multisensory speech perception in an illusory context (i.e., both increasing and decreasing illusion-type responses to a verbal audio-visual integration task). These findings provide clear evidence that both the superior temporal and parietal areas contribute to multisensory integration processing related to speech perception. Specifically, STS seems fundamental for the temporal synchronization and integration of auditory and visual inputs. For its part, posterior parietal cortex (PPC) may adjust the arrival of incoming audio and visual information to STS thereby enhancing their interaction in this latter area.